Empowerment of Women and Children to Realize Justice and Equality from a Gender Perspective - Abner Herry Bajari; Yusuf Gabriel Maniagasi; Semuel Risal; Maddi; Nimbrot Waniopi (Jurnal Multidisiplin Madani, 2023)
Cases of violence against women and children in Indonesia continue to increase from year to year. At the same time, the government issued various policies to overcomeproblemTherefore, the government, both from the national level to the local level, has broad authority to deal with cases of violence that occur. This study explores the phenomenon that occurs in violence against women and children which is then linked to the Child Protection Index (IPA) and the Gender Development Index (IPG) which have not yet been identified to reach global achievement targets for human development based on UN and WHO indicators. This study uses a qualitative research approach to describe various phenomena related to the topic being studied. Our results show that level the province has formedDP3AKB to implement various policies, as well as development and empowerment programs for women and children. However, the performance and role of the DP3AKB institution in prioritizing women's empowerment through gender mainstreaming (PUG) and child protection have not yet reached the target as indicated by the Papua Province IPA and IPG figures which are still far behind compared to other provinces in Indonesia. The reason is that structural and cultural factors dominate in empowering women and children in Papua Province. So that to realize gender equality and the creation of justice, equality, independence, and welfare of women and children in Papua, it must be supported by consistent, targeted policies, and collaboration of stakeholders through the role of "three furnaces" (Government, Religion, and Customs) to realize justice from a gender perspective